Educational work with students through involvement in sectional physical education classes - Pavliuk, Iryna; Kulhuk, Dmytro (My University, 2026)
The article substantiates the educational potential of sectional physical education classes in higher education institutions. It is proved that the sectional form, based on voluntariness and individualization, increases students’ motivation for physical activity and promotes a value-based attitude toward health. The pedagogical conditions for effective educational influence are determined. The study highlights the role of sectional classes in developing moral and volitional qualities, social and communicative competencies, and self-control skills. Sectional physical education is considered an essential component of the educational system in higher education institutions. У статті обґрунтовано освітній потенціал секційних занять з фізичного виховання у вищих навчальних закладах. Доведено, що секційна форма, заснована на добровільності та індивідуалізації, підвищує мотивацію студентів до фізичної активності та сприяє формуванню ціннісного ставлення до здоров'я. Визначено педагогічні умови ефективного освітнього впливу. У дослідженні висвітлено роль секційних занять у розвитку морально-вольових якостей, соціально-комунікативних компетенцій, навичок самоконтролю. Секційне фізичне виховання вважається невід'ємною складовою освітньої системи у вищих навчальних закладах.
Keywords: personal development; educational work; student youth; фізичне виховання; секційні заняття; виховна робота; учнівська молодь; особистісний розвиток; кафедра фізичного виховання; кафедра фізичного виховання; кафедра фізичного виховання